Are you triggering? - Tan, King Hiyang (2010)
Technology provides a tool for solving instructional problems. However, technology integration into instructional design requires creative and strategic effort. Current education focus is on student-centred learning. To motivate student participation and instil meaningful learning require flexible and nonlinearly designed interface. High skill level and advance technological mastery is not an ultimate necessity. Trigger for example, is a wonderful gadget embedded inside Powerpoint® that can assist teachers to transform into a technological expert. Trigger allows object/s to be animated only when a specific object on the Slide Show is clicked, hence triggering the animations. Trigger can transform your instructional material into dynamic, flexible and interactive learning support materials. This paper is intended to share the skill and pedagogical knowledge of integrating trigger into slide presentation. Basic steps is demonstrated to allow for mastery experience. A few creative and effective applications of triggers into instructional materials have been suggested. Hopefully, such experiences will trigger the reader to explore further regarding the magic of triggering.